Анализ показателей суточного мониторирования ЭКГ и АД у больных ЮРА - Кутузова, Л.А. (Таврический медико-биологический вестник, 2010)
Представлено комплексне дослiдження стану серцево-судинної системи у хворих на ЮРА, по даним суточного монiторiнгу. Проведенi науковi дослiдження дозволили виявити комплекснс прогностичнi показники ЭКГ, АТ та ЧСС пiд впливом вегетативних механизмiв гомеостазу та застосування як додаткових крiтерiїв дiагностики визначної патологiї. Complex research of a condition of the сardiac vascular sistem at the 119 of juvenil rheumatoid arthritis of the day monitoring are presented. Scientific research done allowed to work out complex prognostic indices EKG, AP, RCC under influence of vegetative mechanisms of provision of a homeostasis and as additional criteria diagnostics of this pathology.